Towards the rule of law in China : social diversification and the power system / Weidong Ji ; translated by Xi Lin. - Ji, Weidong, 1957- (Cambridge University Press, 2021)
Growing up in China while educated in Japan and the US, the author has in the past few decades both witnessed and actively participated in the historical process of legal transformations in contemporary China. Through a series of academic contributions, as well as meetings, activities and memberships with policymakers and practitioners, the author has spared no effort in applying his theoretical scholarship to real, concrete practices. He has made significant contributions to the building of a rule-of-law system in China, with great social influences. The publishing of this book is to share with English-speaking readers his insights, experiences, and practices related to the institutional undertaking of building the rule of law in China. It offers a legal perspective on some of the cutting-edge issues in our society at large (e.g. risk and uncertainty, AI network, the COVID-19 pandemic, and big data).